COMPOSITION AND STRUCTURE OF THE OCTOCORAL COMMUNITY IN BAJOS DE SANCHO PARDO, LOS COLORADOS REEF, CUBA - Pérez-Angulo, Alejandro (2011)
The composition and structure of octocoral communities was studied in five locations in Bajos de Sancho Pardo (Los Colorados reefs (NW Cuba)) in August 2010. Quadrants measuring one square meter were used as sampling units. A total of 11 fore reefs, two rear zones and one reef crest were studied. Thirty-four species of gorgonians were identified in 2687 colonies. Predominant species included Pseudopterogorgia americana and Pseudopterogorgia elisabethae in the fore reef zone, Briareum asbestinum and Pseudopterogorgia bipinnata in the rear reef, and Gorgonia ventalina and Plexaura homomalla in the reef crest. Significant differences (P = 0.05) were found in the density of gorgonians between fore reef stations. Based on the results of the heterogeneity and evenness indexes, it can be inferred that 79% of the stations were consistent with favorable or very favorable environments and 64% with constant or nearly constant environments. Hydrodynamic stress was low in 79% of the stations, while it was moderate to high in shallow areas of the crest and fore reef. The overall condition of the octocoral community was good according to recorded values of species density and abundance, although it is evident that in the western areas there is greater coverage by fleshy macroalgae, which may be a limiting factor for growth.